Electrostatic interactions in virus removal by ultrafiltration membranes - Gentile, Guillermina José (2020)
Ultrafiltration membranes are increasingly used in potabilization to remove viral particles. This removal is controlled by electrostatic repulsion, attachment and size exclusion. The effect of electrostatic interaction in virus filtration was investigated. Our work included characterization of bacteriophage PP7 and polyethersulfone membrane with respect to size and surface charge; the removal of this bacteriophage at laboratory scale by ultrafiltration membrane process and the mechanism and limitations were analyzed and discussed under DLVO and XDLVO theories. A partial removal of the bacteriophage was achieved; however, enhanced separation may be achieved considering that the process is affected by the aqueous matrix. The presence of divalent cations diminished the effectiveness of the procedure as opposed to monovalent cations and species with amphoteric behavior such as bicarbonate. DLVO and XDLVO predicted the interactions studied between bacteriophage PP7 and polyethersulfone membrane.